Combretum hypopilinum exhibited anti-inflammatory activity in LPS-stimulated RAW 264.7 murine macrophages through inhibition of inflammatory mediators and apoptosis - Kokou Idoh, Kossivi Dosseh, Mrinmoy Gautam, Tchazou Kpatcha, Natarajan Manikandan, Amegnona Agbonon, Muthiah Ramanathan, Messanvi Gbeassor (Journal of Applied Pharmaceutical Science, 2023)
This study has investigated the effects of Combretum hypopilinum on lipopolysaccharide (LPS)-induced inflammation in RAW 264.7 cells. Dried root bark of C. hypopilinum was extracted with dichloromethane, ethyl acetate, and ethanol to give three extracts. To select the most protective extract, RAW 264.7 cells were treated with each extract (10, 20, 40, and 80 μg/ml) in the presence or absence of LPS (1 μg/ml) and incubated for further 24 hours. To investigate the anti-inflammatory effect of ethyl acetate extract (EaE) which was the most protective extract, RAW 264.7 cells were treated with EaE (10, 20, 40, and 80 μg/ml) 1 hour before activation with LPS (1 μg/ml) and incubated for further 24 hours. Effects of EaE on the production of inflammatory mediators [tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, IL-10, and nitric oxide (NO)] and activities of caspase-3, caspase-8, and caspase-9 were measured. Results showed that LPS induced overproduction of pro-inflammatory cytokines and NO. However, treatment with EaE increased the production of IL-10 and decreased the production of TNF-α, IL-1β, and IL-6 and the release of NO. Moreover, EaE decreased the activities of caspase-3 and caspase-8. Our results indicate that C. hypopilinum inhibited LPS-induced apoptosis and inflammation through inhibition of the production of inflammatory cytokines and mediators and inhibition of apoptosis triggered by LPS.
Keywords: Combretum hypopilinum, inflammatory cytokines, inflammation, lipopolyssacharide, apoptosis, RAW 264.7 cells